Spatial development and inter-regional imbalances in social infrastructure in northern province of sri lanka - Mathivathany, V. (university of Jaffna, 2014)
Social Infrastructure is a subset of the infrastructure sector and typically includes assets that accommodate social services. They include health facilities, educational facilities and public amenities which are aspects that focus on the community. Northern region is one of the Provinces of Sri Lanka. This has more disparities in social infrastructure facilities among the regions. The absence of adequate infrastructure facilities also is one of the major barriers for regional development. The coverage and quality of the social infrastructure are the major constrain on the community development in many districts in Northern Province. Therefore, in this study social infrastructure facilities are analyzed. This paper focuses social Infrastructure the identification of the regional disparities in terms of social infrastructure through applying a Spatial Multivariate Technique. Further, this paper would also propose an appropriate spatial strategy to minimize the spatial disparities in order to achieve equitable development or sustainable community development. Information was gathered through visit to areas, and relevant documents for the extensively study. The finding of research reveals that all social infrastructure facilities are highly concentrated in the Kilinochchi district while other districts have less concentration. So If Northern Province has equal concentrate more on social infrastructure in all districts, it can minimize achieve equitable development or sustainability social development. The social infrastructure is an important element in community and regional development. the present situation of for regional development in Northern province of Sri Lanka and This study was carried out by several indicators of regional development.The finding of research reveals that all social infrastructure facilities are highly concentrated in the Kilinochchi district while other districts have less concentration. So the functionally dynamic core region in the province lies in Kilinochchi. Most of the other areas have become socially backward.If Northern Province has equal concentrate more on social infrastructure in all districts, it can minimize achieve equitable development or sustainability social development.
Keywords: Social infrastructure; Equitable development; Sustainable community development; Spatial development